Understanding sentence structure an introduction to English syntax - Tortora, Christina (Linguistics in the world, 2018)
This book is for people who have never thought about syntax, and who don't know anything about grammar, but who want to learn. Assuming a blank slate on the part of the reader, the book treats English grammar as a product of the speaker's mind, and builds up student skills by exploring phrases and sentences with more and more complexity, as the chapters proceed.